Design of a Modular Green Closed Internal Cooling Turning Tool for Applications - Wu, Tao; Li, Tianjian; Ding, Xiaohong; Chen, Hong; Wang, Lei (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
Green machining has been aggressively pursued in the manufacturing industry in recent years. Dry or clean cutting without the hazards of cooling liquid, and their abilities to monitor thermal impact on turning tools in real time have been very appealed to the manufacturing industries. In this study, a modular green closed internal cooling turning tool is presented, in which coolant channel is designed only between an insert and an adaptor. The insert is grouped with the adaptor and designed as a Plug-and-Play component in cooling circuit. Thermal-fluid-structural coupling analysis is employed to evaluate the effects of the internal cooling system with machining process constraints. The numerical simulation results demonstrate that the newly designed internal cooing turning tool could effectively decrease the tool temperature. Preliminary experiments have further proved the effectiveness of the modular green closed internal cooling turning tool system. The study has potentially great significance in improving tooling performance, as well as achieving environmental friendly, economical and sustainable machining.